PENGARUH PROPORSI PISANG KEPOK PUTIH (Musa balbisiana T. BBB) DAN DAGING AYAM TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK PATTIES AYAM PISANG - Hadinoto, Joselyn Tifanny; Utomo, Adrianus Rulianto; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2015)
The research design used was single factor Randomized Design Group (RAK), with 7 (seven) treatment proportion of white kepok banana and chicken breast meat, with 15%,20%, 25%, 30%, 35%, 40%, and 45% of kepok white banana concentration . Each treatment are repeated 4 (four) times. The parameters tested are water content, water holding capacity, juiciness, texture value (hardness and cohesiveness), starch content, protein content, and organoleptic testing (colour, texture, and taste). The data obtained will be analyzed with ANOVA (Analysis of Variance) at Î± = 5% in order to determine whether there is a real effect among parameters of the study. If there is any real effect will be followed by DMRT (Duncanâ€™s Mutiple Range Test) for determining the level of treatment that gives a real difference. Best treatment is choosen from spiderweb graphic. The research data showed that additioning â€œkepok putihâ€ banana gave real effect to water content, water holding capacity, juiciness, cohesiveness, starch content, protein content, and organoleptic testing (colour, texture, and taste). A level panelists for color, texture, and taste in the best sense is on concentration of 30% â€œkepok putihâ€ banana, with 61,6225 Â± 3,2995% water content level, 97,0720 Â± 0,24% water holding capacity level, 18,0266 Â± 1,41% protein content, 5,6850 Â± 2,18% starch content, 11,43% fiber content, hardness (texture value) 6.232,531Â±948,48 g, cohesiveness (texture value) 1,3850 Â± 0,35, with level of panelist of colour 4,93, level of texture 4,96, and level of taste 5,25.